A gigabit/s indoor optical wireless system for Home Access Networks - Minh, H; O'Brien, D; Faulkner, G (2010)
This paper introduces the design and implementation of a 1.25 Gbit/s indoor cellular optical wireless communications system. This forms part of a European community funded project on Home Access Networks (OMEGA). The system includes multiple communications cells with the capability of fast handover to provide seamless communications suitable for in-home use. In this paper we report a demonstration of a bi-directional 1.25 Gbit/s system which can operate up to 4m without error under normal office lighting conditions. In addition HD video streams were successfully transmitted between computers using the system. © 2010 IEEE.